First Record of Anguillid Herpesvirus 1 Linked to a Mass Mortality Event in Shortfin Eel (Anguilla bicolor) in Indonesia - Romadhona, Ekky Ilham; Widantara, Handang; Aslia, Aslia; Megawati, Novi; Ardiansyah, Arif Rahmat; Larassagita, Annisa Fitri; Dewi, Kiki Mariya; Farman, Aditia; Chaidir, Iding; Sujatmiko, Wisnu; Yaniharto, Dedy; Budiardi, Tatag; Aliah, Ratu Siti; Sutanti, Sutanti (Jurnal Medik Veteriner, 2025)
Anguillid herpesvirus 1 (AngHV-1), a member of the Alloherpesviridae family, is known to cause high mortality in both wild and farmed eels. Notably, no cases of AngHV-1 infection in Indonesia until June 2023, when a significant mortality rate exceeding 75% among cultured glass eels was documented in Bogor, Indonesia. This study investigated the outbreak by collecting 30 diseased fish from multiple cultured tanks to examine clinical symptoms, histopathological changes, and viral presence through PCR targeting the viral DNA polymerase gene. Hemorrhagic lesions in the abdomen and anal regions were the primary clinical symptoms. Histopathological examination revealed hyperplasia, fusion, and epithelial lifting of the gill secondary lamellae. PCR, using 394 bp primer specific for AngHV-1, confirmed 100% infection among the collected samples, indicating rapid viral transmission within the rearing environment. Phylogenetic analysis of partial DNA polymerase amino acid sequences showed that Indonesian AngHV-1 isolate is genetically diverse and shares similarities with strains from China, Taiwan, Canada, and several European countries, suggesting the emergence of a novel strain. This study highlights the urgent need for enhanced biosecurity measures to curb AngHV-1 spread in the Indonesian eel aquaculture sector.